2021
DOI: 10.3390/nu13051451
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perioperative Administration of Probiotics on Colorectal Cancer Surgery Outcomes

Abstract: The perioperative care of colorectal cancer (CRC) patients includes antibiotics. Although antibiotics do provide a certain protection against infections, they do not eliminate them completely, and they do carry risks of microbial resistance and disruption of the microbiome. Probiotics can maintain the microbiome’s balance postoperatively by maintaining intestinal mucosal integrity and reducing bacterial translocation (BT). This review aims to assess the role of probiotics in the perioperative management of CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
0
16
0
3
Order By: Relevance
“…Table 4 illustrates examples from human clinical trials [ 131 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Not surprisingly, the best outcomes occur when there is a clear understanding of the specific microbes, genes, metabolic changes, and installation conditions that are needed to support microbiome-driven physiological benefits.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…Table 4 illustrates examples from human clinical trials [ 131 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. Not surprisingly, the best outcomes occur when there is a clear understanding of the specific microbes, genes, metabolic changes, and installation conditions that are needed to support microbiome-driven physiological benefits.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…In recent years, probiotics have gradually become a hot spot in general surgery research (Pitsillides et al, 2021;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, probiotics have gradually become a hot spot in general surgery research (Pitsillides et al., 2021; Zhang et al., 2021). Past meta‐analysis literature showed that probiotics reduced infection and inflammatory reactions in patients after colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to use probiotics in the treatment of colorectal cancer and to reduce the risk of its development. The analysis of randomised trials shows that using probiotics, especially Lactobacilli and Bifidobacterium species, reduces postoperative complications and accelerates patient recovery [ 118 ]. Faghfoori et al proved that some Bifidobacteria species produce substances that affect the activation of apoptotic pathways in human colorectal cancer cells (HT-29 and Caco-2 cell lines) but highlighted the need for further research in this area [ 119 ].…”
Section: Colorectal Cancermentioning
confidence: 99%